Improving of Self-Care Deficit Through Community As Partner to Enhance Personal Hygiene in Patients with Mental Disorders - Sulaihah, Sitti; Suhron, M; Amir, Faisal; Rahayu, Atik Puji; Marniyah (Jurnal Kesehatan dr. Soebandi, 2026)
Background: Self-care deficit is one of the main problems that arise in clients with chronic mental disorders, who frequently neglect their self-care, this condition is a symptom of negative behavior and causes clients to be ostracized both in the family and society. Based on the results of a preliminary study at the Bani Amrini Mental Health Center through observation of all People with Mental Disorders (ODGJ) patients, it was found that patients experienced poor personal hygiene because there was only 1 nursing home officer who supervised 35 patients. The purpose of the study was to analyze the differences in community as partners towards the fulfillment of personal hygiene in patients with self-care deficits. Methods: The design of this study was pre-experimental with a one group pre-post-test approach. The population used was People with Mental Disorders (ODGJ) at the Bani Amrini Mental Health Foundation with a sample size of 35 using the Total Sampling technique.The independent variable was “community as partner” (through screening assessments, personal hygiene education, practical demonstrations, independent hygiene activities, and evaluation sessions) and the dependent variable was the fulfillment of personal hygiene. Data sources were collected through observations of the fulfillment of personal hygiene. Results:    The results of the normality test using the Shapiro–Wilk test showed values of 0.045 in the pretest and 0.026 in the posttest; therefore, the Wilcoxon Signed Rank Test was subsequently performed with a significance level (α) of 0.05. The test results obtained a P-value (0.000) for fulfillment  personal hygiene People with Mental Disorders (ODGJ) patients before and after being given community as partner showed that there was a difference between community as a partner in improving fulfillment personal hygiene. Conclusions: People with Mental Disorders (ODGJ) patients. The researcher's suggestion is that it is important to implement community as partner therapy continuously to improve the fulfillment of personal hygiene for People with Mental Disorders (ODGJ) patients so that it is expected to help accelerate the recovery and healing process for People with Mental Disorders (ODGJ) patients at the Bani Amrini Mental Health Foundation.